Implicit Approximate Crank–Nicolson Theory for Anisotropic Ferrite Structure Simulation with Enhanced Absorption. Issue 11 (4th October 2021) - Wu, Peiyu; Xie, Yongjun; Jiang, Haolin; Di, Hanyi; Natsuki, Toshiaki
Abstract: To simulate ferrite structures with anisotropic characteristics efficiently, an unconditionally stable implementation is proposed by incorporating the approximate Crank–Nicolson (CN) theory and a complex‐frequency‐shifted perfectly matched layer (CFS‐PML) formulation in the finite‐difference time‐domain lattice. More specifically, the proposed implementation combines the CN approximate factorization splitting procedure with bilinear transformation in the z ‐domain within the CFS‐PML regions. To simulate the unique anisotropic characteristic of the ferrite structure, the auxiliary differential equation (ADE) method, which is modified at the integer time step, is introduced during the formulation. Numerical examples are presented to demonstrate the effectiveness and efficiency theoretically and experimentally. According to the results, it can be concluded that the proposed scheme takes full advantage of the approximate CN theory, CFS‐PML formulation, and modified ADE method in terms of the considerable computational accuracy, outstanding absorbing performance, and remarkable efficiency. Moreover, it can be demonstrated that the proposed algorithm can maintain its stability with the dissatisfaction of the Courant–Friedrichs–Lewy condition. Abstract : To simulate ferrite structures with anisotropic characteristic, unconditionally stable implementation is proposed by incorporating the approximate Crank–Nicolson theory and complex‐frequency‐shifted perfectly matched layer formulation. To simulate the unique anisotropic characteristic of ferrite structure, the modified auxiliary differential equations method is introduced. Numerical examples are carried out to demonstrate the effectiveness theoretically and experimentally.